1999
DOI: 10.1161/01.cir.100.22.2267
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Artery Mechanics, Structure, and Extracellular Components in Spontaneously Hypertensive Rats

Abstract: Background-Altered vascular mechanics resulting from changes in collagen and integrins may influence resistance artery structure and function and, therefore, peripheral resistance and blood pressure in spontaneously hypertensive rats (SHR). Methods and Results-Effects of age, angiotensin-converting enzyme inhibition (fosinopril, 10 to 30 mg/kg per day), and AT 1 -receptor antagonism (irbesartan, 50 mg/kg per day) on vascular structure, mechanics, and composition were assessed in SHR. Systolic blood pressure wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
131
0
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(156 citation statements)
references
References 30 publications
20
131
0
5
Order By: Relevance
“…Despite the samples being incubated for 20 hours, thicker samples will require longer for the enzymes to permeate to the centre and thus thinner samples would be expected to be more digested [48].…”
Section: Mechanical Tests and Effects Of Digestionmentioning
confidence: 99%
“…Despite the samples being incubated for 20 hours, thicker samples will require longer for the enzymes to permeate to the centre and thus thinner samples would be expected to be more digested [48].…”
Section: Mechanical Tests and Effects Of Digestionmentioning
confidence: 99%
“…The collagen/ elastin ratio has also been shown to be increased in human resistance arteries from mild essential hypertensive patients. [55][56][57] Moreover, vascular proteoglycan synthesis is also increased by high blood pressure. 58 These changes may contribute to the inward remodeling of the arterioles found in hypertension.…”
Section: Composition Of the Extracellular Matrix (Ecm) In The Vasculamentioning
confidence: 99%
“…Previous studies have shown that av integrin levels are enhanced on the dysfunctional endothelium in spontaneously hypertensive rats, but not in controls. 25 This therefore allowed the evaluation of FLT-1 activity and RGD targeting with a single vector system in a disease model. We used short exposure times of virus:vessel (30 and 60 min), since this is a limitation for vascular gene delivery.…”
mentioning
confidence: 99%